Recommendations for participation in competitive and leisure time sport in athletes with cardiomyopathies, myocarditis, and pericarditis: position statement of the Sport Cardiology Section of the European Association of Preventive Cardiology (EAPC) - Pelliccia, A.; Ekker Solberg, E.; Papadakis, M.; Adami, P. E.; Biffi, A.; Caselli, S.; La Gerche, A.; Niebauer, J.; Pressler, A.; Schmied, C. M.; Serratosa, L.; Halle, M.; et al. (European Heart Journal, 2019)
Myocardial diseases are associated with an increased risk of potentially fatal cardiac arrhythmias and sudden cardiac death/cardiac arrest during exercise, including hypertrophic cardiomyopathy, dilated cardiomyopathy, left ventricular non-compaction, arrhythmogenic cardiomyopathy, and myo-pericarditis. Practicing cardiologists and sport physicians are required to identify high-risk individuals harbouring these cardiac diseases in a timely fashion in the setting of preparticipation screening or medical consultation and provide appropriate advice regarding the participation in competitive sport activities and/or regular exercise programmes. Many asymptomatic (or mildly symptomatic) patients with cardiomyopathies aspire to participate in leisure-time and amateur sport activities to take advantage of the multiple benefits of a physically active lifestyle. In 2005, The European Society of Cardiology (ESC) published recommendations for participation in competitive sport in athletes with cardiomyopathies and myo-pericarditis. One decade on, these recommendations are partly obsolete given the evolving knowledge of the diagnosis, management and treatment of cardiomyopathies and myo-pericarditis. The present document, therefore, aims to offer a comprehensive overview of the most updated recommendations for practicing cardiologists and sport physicians managing athletes with cardiomyopathies and myo-pericarditis and provides pragmatic advice for safe participation in competitive sport at professional and amateur level, as well as in a variety of recreational physical activities.